Analisis Ayat Al-Qur'an tentang Kemiskinan: Kajian Tafsir Tematik Q.S. al-Żāriyāt Ayat 19: The Analysis of Quranic Verses on Poverty: A Thematic Tafsir Study of Surah al-Żāriyāt Verse 19 - Ihwan Wahid Minu; Achmad Abubakar; Sohrah, Sohrah (AL-QIBLAH: Jurnal Studi Islam dan Bahasa Arab, 2025)
This study aims to find out how Q.S. al-Żāriyāt verse 19 describes the condition of poverty in the perspective of Islam, to find out what the relationship is between this verse and the principles of welfare in the perspective of thematic interpretation, and to find out how Islam's solution to poverty is reflected in Q.S. al-Żāriyāt verse 19. This research is a library research. The results of this study are that Q.S. al-Żāriyāt verse 19 describes poverty in Islam as a condition that not only involves material deficiencies, but is also related to social, moral, and spiritual aspects. In the thematic interpretation of Q.S. al-Żāriyāt verse 19, the principles of welfare in Islam contained in this verse emphasize the importance of attention to those who do not beg, and the fulfillment of the rights of the poor as part of a greater social responsibility. In Q.S. al-Żāriyāt verse 19, there is an emphasis on paying attention to two types of poverty, namely those who beg and those who do not beg. Islam emphasizes the obligation to provide assistance to both, by maintaining their honor and paying attention to their overall welfare and offering solutions to create equitable prosperity in society.